Palladium‐Catalyzed Decarbonylative Rearrangement of N‐Allenyl Seleno‐ and Tellurocarbamates. Issue 6 (2nd September 2014) - Shiro, Daisuke; Nagai, Hiroyuki; Fujiwara, Shin‐ichi; Tsuda, Susumu; Iwasaki, Takanori; Kuniyasu, Hitoshi; Kambe, Nobuaki
ABSTRACT Decarbonylative rearrangement of seleno‐ and tellurocarbamates carrying an allenyl group on the nitrogen was found to proceed in the presence of a palladium catalyst to afford 3‐chalcogeno‐1‐azadienes. This transformation may involve oxidative addition of Pd to a carbon–chalcogen bond, decarbonylation from a carbamoylpalladium unit (R2N‐C(O)‐PdChPh: Ch = Se or Te), Pd shift, and reductive elimination.